Neurophysiological effect of the Rh factor. Protective role of the RhD molecule against Toxoplasma-induced impairment of reaction times in women - Flegr, Jaroslav; Novotná, Martina; Lindová, Jitka; Havlíček, Jan (Neuro-endocrinology letters, 2008)
BACKGROUND: The biological function of RhD protein, a major component of the Rh blood group system, is largely unknown. No phenotypic effect of RhD protein, except its role in hemolytic disease of newborns and protective role against Toxoplasma-induced impairment of reaction times in men, has been described. METHODS: Here we searched for a protective effect of RhD positivity against Toxoplasma-induced prolongation of reaction times in a set of 110 male and 226 female students of the Faculty of Science tested for latent toxoplasmosis and concentration of testosterone in saliva. RESULTS: RhD-positive subjects have been confirmed to be less sensitive to the influence of latent toxoplasmosis on reaction times than Rh-negative subjects. While a protective role of RhD positivity has been demonstrated previously in four populations of men, the present study has shown a similar effect in 226 female students. Our results have also shown that the concentration of testosterone in saliva strongly influences (reduces) reaction times (especially in men) and therefore, this factor should be controlled in future reaction times studies. CONCLUSIONS: The observed effects of RhD phenotype could provide not only a clue to the long-standing evolutionary enigma of the origin of RhD polymorphism in humans (the effect of balancing selection), differences in the RhD+ allele frequencies in geographically distinct populations (resulting from geographic variation in the prevalence of Toxoplasma gondii), but might also be the missing piece in the puzzle of the physiological function of the RhD molecule.
Keywords: financování organizované; dospělí; Animals; Female; krevní skupiny - systém Rh-Hr; novorozenec; Toxoplasmosis; reakční čas; Adult; ženské pohlaví; testosteron; lidé; Infant, Newborn; Toxoplasma; Financing, Organized; Male; Neuroprotective Agents; Reaction Time; toxoplazmóza; Testosterone; Rh-Hr Blood-Group System; zvířata; mužské pohlaví; neuroprotektivní látky; Humans